Potensi Lumpur Sawit (SOLID) Sebagai Pakan Ruminansia di Kabupaten Pelalawan Provinsi Riau - Kodri Yanto; Dewi Febrina (Agricultural Faculty, 2008)
Potential of palm oils waste (solid) as ruminant feed in Pelalawan district of Riau ProvinceABSTRACT. The objective of this study was to know potential of solid waste in Pelalawan district, Riau province. Research was carried out from December 2007 January 2008 in Pelalawan district by using 4 factories of Elaeis guineensis (PKS). The four factories that were used for data collection were PT. Multi Palma Sejahtera (MPS), PT. Inti Indo Sawit Subur (IIS), PT. Sinar Agro Raya (SAR) and PT. Musim Mas (MM). The results of study showed that solid waste in Pelalawan district of Riau province had a great potential. Production of solid waste in Pelalawan district was around 76.176 tons/year and carrying capacity was 5.132 animals unit. Farmers will use solid waste at large quantity if they raise livestock in commercially, for instance for fattening purpose. The strategies which can be applied to maximize solid waste utilization are through partnership between farmers and factories or local government pihak PKS.